Differences in ecological structure, function, and native species abundance between native and invaded Hawaiian streams. Issue 6 (1st September 2013) - Holitzki, Tara M.; MacKenzie, Richard A.; Wiegner, Tracy N.; McDermid, Karla J.
Abstract : Poeciliids, one of the most invasive species worldwide, are found on almost every continent and have been identified as an "invasive species of concern" in the United States, New Zealand, and Australia. Despite their global prevalence, few studies have quantified their impacts on tropical stream ecosystem structure, function, and biodiversity. Utilizing Hawaiian streams as model ecosystems, we documented how ecological structure, function, and native species abundance differed between poeciliid‐free and poeciliid‐invaded tropical streams. Stream nutrient yields, benthic biofilm biomass, densities of macroinvertebrates and fish, and community structures of benthic algae, macroinvertebrates, and fish were compared between streams with and without established poeciliid populations on the island of Hawai′i, Hawaii, USA. Sum nitrate (ΣNO3 − = NO3 − + NO2 − ), total nitrogen, and total organic carbon yields were eight times, six times, and five times higher, respectively, in poeciliid streams than in poeciliid‐free streams. Benthic biofilm ash‐free dry mass was 1.5× higher in poeciliid streams than in poeciliid‐free streams. Percentage contributions of chironomids and hydroptilid caddisflies to macroinvertebrate densities were lower in poeciliid streams compared to poeciliid‐free streams, while percentage contributions of Cheumatopsyche analis caddisflies, Dugesia sp. flatworms, and oligochaetes were higher. Additionally, mean densities of native gobies were two times lower in poeciliid streams than in poeciliid‐free ones, with poeciliid densities being approximately eight times higher than native fish densities. Our results, coupled with the wide distribution of invasive poeciliids across Hawaii and elsewhere in the tropics, suggest that poeciliids may negatively impact the ecosystem structure, function, and native species abundance of tropical streams they invade. This underscores the need for increased public awareness to prevent future introductions and for developing and implementing effective eradication and restoration strategies.